Barriers and enablers to the implementation of infection prevention and control guidance in a Ugandan healthcare facility – a theory-informed qualitative study to guide intervention design - Kalule, Andrew Owen; Currie, Kay; Price, Lesley (International Journal of Infection Control, 2025)
Implementing Infection Prevention and Control (IPC) guidance is crucial for reducing healthcare-associated infection (HAI) rates. However, achieving behavioural and organisational change is necessary for successful implementation. To understand these changes, it is important to identify the barriers and facilitators to IPC implementation, supported by theoretical analysis. This paper presents the second stage of a study conducted in Uganda, aiming to analyse barriers and enablers to IPC guideline implementation and provide preliminary recommendations for intervention design. Interviews with frontline healthcare workers were conducted, and qualitative content analysis helped identify specific barriers and enablers. The Theoretical Domains Framework (TDF) was used to categorise and map these factors to the BCW/COM-B model, enabling the identification of intervention functions supporting IPC implementation. The findings highlighted various important factors influencing IPC implementation, including social influences, environmental context and resources, knowledge, skills, professional role and identity, behavioural regulation, memory, attention and decision processes, goals, beliefs about capabilities, beliefs about consequences, intentions, emotion, and reinforcement. All components of the COM-B model (Capability, Opportunity, Motivation) were deemed significant in IPC implementation. Key intervention functions such as enablement, environmental restructuring, training and education, persuasion, and incentivization were identified as potentially useful for designing interventions to improve IPC implementation. In conclusion, the analysis emphasized the interconnectedness and importance of capability, opportunity, and motivation in adopting IPC guidance in such contexts. The study offers recommendations for future interventions, including education and training programs, leveraging memory and attention, addressing beliefs about consequences, and improving social influences and support systems. These insights can guide the development of effective strategies to enhance IPC implementation.